Perancangan Media Pembelajaran Perakitan Komputer Menggunakan Aplikasi Augmented Reality di SMKN 1 Tantom Angkola Sumatra Utara - Amir Salim Khairul Rijal ‎; Derta, Sarwo (Indonesian Research Journal on Education, 2023)
Every innovation is created to provide positive benefits for human life. Providing many conveniences, as well as a new way of carrying out human activities, especially in the field of information technology has enjoyed many benefits brought about by the innovations that have been produced in the last decade.Along with the passage of time education is also growing, the development of science and technology encourages reform efforts in the use of technological results in the teaching and learning process. Learning media can be said as a learning tool, namely everything that can be used to stimulate thoughts, feelings, attention and abilities or students' skills so that it can encourage the learning process. This limitation is still quite broad and in-depth, including the understanding of sources, environment, people and methods used for the purpose of learning. Media for learning Information and communicationtechnology is made using "powtoon" and "added" application, namely linktree. The type of research used is the type of research and development (Research and Development). The R&D model used is the 4-D (four D) version, namely Define, Design, Develop, and Disseminate, using the Luther-Sutopo multimedia development model, which consists of Concept, Design, Materials Collecting, Assembly , Testing, andDistribution.‎ Based on the results of the research that has been done, it can be concluded that theresulting application can be utilized and suitable for use by students and teachers in the subjectsconcerned. The results of the validity test by experts on the android-based learning media obtained an average value of 0.88, namely valid, the practicality test got an average value of 0.88 with a very high category, and the effectiveness test got an average value. average 0.80 with very effective category.